Managing and Organizing - Loladze, Ivane N. (Journals of Georgian Geophysical Society, 2022)
The globalization of the business environment means that companies are moving to different parts of the world to serve different markets. Therefore, it was necessary to develop performance management (PM) functions that facilitate the development of processes and activities that, in turn, meet the goals and objectives of the organization. The study is devoted to the analysis of the prospects for PM in the modern business environment and the complexity of its implementation. At the same time, the commercialization of scientific achievements, in particular, geophysical research, support for economic activity and innovation in management has become of great importance. This article provides solutions to these problems.